Interaction of norsecurinine-type monomeric and dimeric alkaloids with α-tubulin: a molecular docking study - Gérard Vergoten; Christian Bailly (Exploration of Drug Science)
Aim: New microtubule-targeting agents are needed to improve cancer treatment. The recent characterization of the anticancer alkaloid securinine as a tubulin-binding agent prompted us to explore the interaction of related monomeric and dimeric analogues with tubulin. The interaction between the α/β-tubulin dimer and alkaloids fluevirines A–F and flueggenines A–I, isolated from the bush Flueggea virosa (Roxb. ex Willd.) Royle, was investigated using molecular docking. Methods: Two molecular models were initially compared for the binding of securinine to α/β-tubulin. The pironetin-binding site model (5FNV) was selected for the subsequent docking analysis with all compounds. Empirical energies of interaction (ΔE) were measured and compared. Results: Fluevirine A has been identified as a potent tubulin binder. This dimeric alkaloid formed more stable complexes with tubulin than the monomeric counterparts, such as fluevirines B–D. The bis-indole derivative fluevirine E also provided more stable complexes than (nor)securinine. The study was extended to the dimeric alkaloids flueggenines A–I and three compounds were identified as potential tubulin binders: the polycyclic product flueggenine B, the norsecurinine-indole hybrid flueggenine E, and the norsecurinine dimer flueggenine I. This later compound proved to be well adapted to fit into the pironetin site of tubulin, extending its two norsecurinine units between the colchicine-binding area and the pironetin site, in close proximity to the pironetin-reactive cysteine-316 residue. Structure-binding relationships were delineated. Conclusions: The study identifies the dimeric alkaloids fluevirine A and flueggenine I as potential α-tubulin binding agents. For the first time, dimeric alkaloids including two C-C connected norsecurinine units are characterized as tubulin ligands. The study contributes to a better understanding of the mechanism of action of Flueggea alkaloids and should help the design of anticancer analogues targeting the pironetin site of α-tubulin.